Analyzing an error in the synchronization of hydraulic motor speed under transient operating conditions - Havrylenko, Oleksii; Kulinich, Serhii (Eastern-European Journal of Enterprise Technologies, 2019)
A hydraulic drive with two hydraulic cylinders was considered in which the rod movement speeds are synchronized by a divider of the working fluid flow. Based on the developed mathematical model, operation of synchronized hydraulic cylinders in transient operating conditions with a sudden change of load on one of the hydraulic cylinders was calculated. Speeds of movement of the hydraulic cylinder rods and pressures in the inter-throttle chambers of the flow divider were determined. It was established that there were variations of pressure in the inter-chamber chambers of the flow divider in the transient conditions of operation of the drive caused by a sudden change of load on the hydraulic cylinders and, as a result, an error of synchronization of speed of movement of the cylinders rods appeared at the initial stage. Relative pressure differential in the inter-throttle chambers reached 1 and the relative difference of speeds of movement reached 0.43. To improve accuracy of synchronization of hydraulic motor movement, a flow divider was proposed with an additional feedback in the pressure differential in the inter-throttle chambers of the divider. The additional feedback was realized through the use of a double-slotted throttling distributor of the spool-valve type. Proceeding from the conditions of a minimum synchronization error, the necessary dependence of change of area of the working slot of the controlled throttles was determined and recommendations on profiling the working slots of the spool throttle were given. It was established by calculation and confirmed experimentally that the use of controlled throttles reduces the error of synchronization of speed of movement of the cylinder rods to 0.27 and the pressure differential in the inter-throttle chambers of the flow divider to 0.53. Harmonics of higher order occurred in a transient process for speed and pressure. They were caused by movement of the spool valve of the double-slot distributor. Presence of harmonics of higher order in variations of pressure and velocity did not significantly affect operation of hydraulic motors since amplitude of these variations was negligible. Reduction of the speed synchronization error is due to simultaneous change of area of the throttle which stabilizes pressure differential and the area of the controlled throttle.